2022
DOI: 10.1029/2021wr031649
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐Temporal Model Variance‐Covariance Approach to Assimilating Streamflow Observations Into a Distributed Landscape Water Balance Model

Abstract: 2 of 20 conditions can play a major role for streamflow predictability for lead times up to 3 months on main Amazonian River tributaries. Over the last couple of decades, an abundance of gauge-measured streamflow (Abaza

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Tian et al. (2022) showed an example of such approach with a spatially explicit error covariance matrix used to assimilate streamflow in a gridded landscape model. A multi‐site configuration will be critical if DAISI is applied to areas where streamflow measurements are limited, hence reducing the effectiveness of data assimilation within DAISI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tian et al. (2022) showed an example of such approach with a spatially explicit error covariance matrix used to assimilate streamflow in a gridded landscape model. A multi‐site configuration will be critical if DAISI is applied to areas where streamflow measurements are limited, hence reducing the effectiveness of data assimilation within DAISI.…”
Section: Discussionmentioning
confidence: 99%
“…ES was originally designed by van Leeuwen and Evensen (1996) to assimilate observations in large gridded models which suggests that DAISI could be extended to a multi-site approach where streamflow from all catchments are assimilated jointly. Tian et al (2022) showed an example of such approach with a spatially explicit error covariance matrix used to assimilate streamflow in a gridded landscape model. A multi-site configuration will be critical if DAISI is applied to areas where streamflow measurements are limited, hence reducing the effectiveness of data assimilation within DAISI.…”
Section: How Can Daisi Be Improved?mentioning
confidence: 99%
“…However, spatiotemporal state updating in distributed hydrological models via streamflow DA remains a challenge due to the large dimensional disparity between the model state space and observation space. One solution is to use spatiotemporal variance‒covariance from simulated climatology models as a surrogate for model error to spatially distribute constraints from gauge measurements (S. Tian et al., 2022).…”
Section: Applications Of Land Data Assimilation In Estimating Land Su...mentioning
confidence: 99%